An Investigation of Response Bias Associated with Electronically Delivered Risk-Tolerance Assessment - John E Grable; Sonya L Britt (Journal of Financial Therapy, 2011)
A randomized experimental study was designed to compare risk-tolerance scores for those who completed a paper-and-pen risk-tolerance assessment instrument (i.e., the control group) to those who answered the same questions using an electronic method. It was hypothesized that the possibility of an electronic bias might be present. Controlling for financial knowledge, which was positively associated with risk tolerance, men were found to report much higher risk-tolerance scores than women when responding to electronically delivered questions. Results suggest that financial therapists ought to consider this possibility as a factor that influences responses to risk assessments, especially as they incorporate additional technological evaluation tools into their practice.
Keywords: Financial Therapy; Financial Planning; Financial Counseling